Appraising gender equity - rethinking the African landscape of proverbia - Chauraya, Efiritha (2016)
This article is a nuanced and systematic gender interrogation and appraisal of African proverb. The article does so in the quest for gender equity as a crucial and critical aspect of human categorizations in modern society. The article offers a rebuttal to the holding views that the African worldview has ‘men exclusive’ and ‘women exclusive’ lives in hierarchical order. The article arrives at the indication that this used to be the order of the day then, but now acknowledges that there is significant crossing of traditional gender boundaries in almost all social activities in most African countries. The article concludes that it is now time the African proverb shakes off its numbness and muteness and responds to the changing social, political and economic transformations that are greeting modern Africa. The researcher is of the view that its time the African proverb transcends time and embraces more gender sensitive ways of human representations. Culture (in which the proverb is embedded) changes and evolves as individuals and communities evolve. There is, therefore, need for the proverb to move with time so that it does not get outmoded. The concern is thus, that, the proverb reflects the dynamism of oral traditions in which it is intertwined.